2005
DOI: 10.1038/nmeth790
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous stalled ribosome nascent chain complexes produced in vivo or in vitro

Abstract: Cotranslational protein maturation is often studied in cell-free translation mixtures, using stalled ribosome-nascent chain complexes produced by translating truncated mRNA. This approach has two limitations: (i) it can be technically challenging, and (ii) it only works in vitro, where the concentrations of cellular components differ from concentrations in vivo. We have developed a method to produce stalled ribosomes bearing nascent chains of a specified length by using a 'stall sequence', derived from the Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 31 publications
5
77
0
Order By: Relevance
“…To produce arrested SH3 and m10 polypeptides exposing the entire SH3 or m10 domains outside the ribosomal exit tunnel, we introduced a C-terminal 41-aa linker. This linker carried the SecM stalling sequence known to arrest translation and was long enough to extend through the entire length of the ribosomal peptide tunnel (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…To produce arrested SH3 and m10 polypeptides exposing the entire SH3 or m10 domains outside the ribosomal exit tunnel, we introduced a C-terminal 41-aa linker. This linker carried the SecM stalling sequence known to arrest translation and was long enough to extend through the entire length of the ribosomal peptide tunnel (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…Once translated, this 18-residue peptide interacts with the exit tunnel of the 50S subunit leading to translation stalling (Nakatogawa and Ito 2001;Yap and Bernstein 2009). The SecM arrest sequence has been shown to be an effective method of anchoring a mature protein to the ribosome immediately following translation in both single-molecule and bulk experiments (Evans et al 2005;Uemura et al 2008). The stalled 70S-SNAP f complex has a half-life of ∼60 min (Evans et al 2005;Tsai et al 2014), so turnover is still observed in longer time courses.…”
Section: Designing the Snap Assaymentioning
confidence: 99%
“…The SecM arrest sequence has been shown to be an effective method of anchoring a mature protein to the ribosome immediately following translation in both single-molecule and bulk experiments (Evans et al 2005;Uemura et al 2008). The stalled 70S-SNAP f complex has a half-life of ∼60 min (Evans et al 2005;Tsai et al 2014), so turnover is still observed in longer time courses. The arrest sequence has two functions in the SNAP assay.…”
Section: Designing the Snap Assaymentioning
confidence: 99%
“…that may affect the binding of TF to ribosome, it is essential to investigate RNCs harboring defined states of nascent chains, and hence to arrest the translation process at selected stages. For this purpose, we improved a method that allows the stalling of nascent chains in E. coli cells followed by the isolation of quantitative amounts of stalled RNCs (19,20). To induce translational arrest, we genetically fused the 3Ј-end of the open reading frames of target genes to a linker encoding both the SecM peptide, which induces translational arrest (21), and additional amino acids (aa) to allow the complete exposure of the target protein at the ribosomal exit site (Fig.…”
Section: Design Of Arrested Nascent Chain Constructs-see Supplementalmentioning
confidence: 99%